2023
DOI: 10.1007/s00431-023-04948-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physical activity patterns from adolescence to young adulthood: the BELINDA study

Abstract: Physical activity (PA) is recognized as a marker of health. The aim was to investigate PA differences from adolescence to young adulthood. European adolescents included in the HELENA study were invited to participate in a follow-up study, 10 years later. The present study included 141 adults (25.0 ± 1.4 years) for whom valid accelerometer data were available in adolescence and adulthood. Changes in PA by sex, weight and maternal education level were explored with interactions. Time spent in sedentary activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Previous studies have reported that people with Down syndrome engage in less physical activity than their peers with intellectual disability (ID) and their peers without disabilities and that most do not meet physical activity guidelines including limiting sedentary time (Izquierdo-Gomez et al 2017;Shields et al 2018;Oreskovic et al 2020). The transition from adolescence to young adulthood is when physical activity levels are known to decline among young adults without disability (Vanhelst et al 2023), but limited data are available on physical activity and sedentary time during this life phase for those with Down syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that people with Down syndrome engage in less physical activity than their peers with intellectual disability (ID) and their peers without disabilities and that most do not meet physical activity guidelines including limiting sedentary time (Izquierdo-Gomez et al 2017;Shields et al 2018;Oreskovic et al 2020). The transition from adolescence to young adulthood is when physical activity levels are known to decline among young adults without disability (Vanhelst et al 2023), but limited data are available on physical activity and sedentary time during this life phase for those with Down syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…The transition from adolescence to young adulthood is when physical activity levels are known to decline among young adults without disability (Vanhelst et al . 2023), but limited data are available on physical activity and sedentary time during this life phase for those with Down syndrome.…”
Section: Introductionmentioning
confidence: 99%